Du lịch teambuilding - Một cách để gắn kết tập thể - Lê, Việt Hà; Nguyễn, Ngọc Linh (2020)
The article is devoted to the problem of development of the Russian tourist market in Vietnam. Statistical data for the last 20 years about the number of Russian tourist arriving in Vietnam is presented. The strengths and weaknesses of tourism in Vietnam is discussed. The way to solve the problem of attracting Russian tourists to Vietnam are suggested.